Genetic sequencing detected the SARS-CoV-2 delta variant in wastewater a month prior to the first COVID-19 case in Ahmedabad (India). (1st October 2022) - Joshi, Madhvi; Kumar, Manish; Srivastava, Vaibhav; Kumar, Dinesh; Rathore, Dalip Singh; Pandit, Ramesh; Graham, David W.; Joshi, Chaitanya G.
Abstract: Wastewater-based genomic surveillance can identify a huge majority of variants shed by the infected individuals within a population, which goes beyond genomic surveillance based on clinical samples (i.e., symptomatic patients only). We analyzed four samples to detect key mutations in the SARS-CoV-2 genome and track circulating variants in Ahmedabad during the first wave (Sep/Nov 2020) and before the second wave (in Feb 2021) of COVID-19 in India. The analysis identified a total of 34 mutations in the spike protein across samples categorized into 23 types. The spike protein mutations were linked to the VOC-21APR-02; B.1.617.2 lineage (Delta variant) with 57% frequency in wastewater samples of Feb 2021. The key spike protein mutations were T19R, L452R, T478K, D614G, & P681R and deletions at 22029 (6 bp), 28248 (6 bp), & 28271 (1 bp). Interestingly, these mutations were not seen in the samples from Sep/Nov 2020 but did appear before the massive second wave of COVID-19 cases, which in India started in early April 2021. In fact, genetic traces of the Delta variant were found in samples of early Feb 2021, more than a month before the first clinically confirmed case of this in March 2021 in Ahmedabad, Gujarat. The present work describes the circulating of SARS-CoV-2 variants in Ahmedabad and confirms the consequential value of wastewater surveillance for the early detection of variants of concerns (VOCs). Such monitoring must be included as a major component of future health protection systems. Graphical abstract: Image 1 Highlights: First detection of delta variant (VOC-21APR-02; B.1.617.2) in the wastewater of India. Treated water showed more prevalence of Delta variant than the non-treated wastewater. WBE is capable to detect and deal with SARS-CoV-2 variants and their cryptic transmission. WW genomic surveillance can aid the decision-making system for public health policies. Delta variant found a month earlier in the wastewater than the first confirmed clinical case. Abstract : Delta variant found a month earlier in the wastewater of Ahmedabad than the first confirmed clinical patient report.